Atopy patch tests as an additional criterion - Samochocki, Zbigniew; Owczarek, Witold; Zabielski, Stanisław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Complex pathomechanism of skin lesions in atopic dermatitis (AD) results in variations of clinical picture and frequent difficulties in diagnosis. The purpose of the study was to evaluate the usefulness of APT with aeroallergens in the diagnosis of AD. The study was conducted among 115 adult patients with AD. The control group was composed of 98 health voluntaries comprised proportionally in terms of age and sex. APT with cat dander allergens, birch pollen, the mixture of house dust mite and 5 grass pollen allergens were performed in both groups. The results were then subjected to statistical analysis. At least one positive reaction to tested allergens was found in 62/115 (53.9%) patients. The control group presented relevant percentage of 6.2 and the difference statistically relevant (p<0.001). Hypersensitivity to house dust mite allergens was observed most often – 45.2%. In case of other airborne allergens results were as followed: birch pollen – 32.2%, grass pollen 22.6% and cat dander – 15.7%. In the control group positive reaction only for house dust mite allergens was observed (p<0.001). 43.5% patients presented positive reaction to only one allergen, the rest 56.5% presented polyvalent allergy to 2-4 allergens. Specificity of conducted tests in comparison to tested allergens amounted over 75%, whereas the sensitivity varied from 18 to 66%. Conclusions: 1. APT characterized by considerable specificity confirm the role of polyvalent contact hypersensitivity to aeroallergens in the development of AD; 2. Positive results of ATP with aeroallergens as a feature observed in majority of patients may constitute an additional criterion of allergic type of AD diagnosis.